Yantra: infrastructures of the sacred and profane in Varanasi, India - Maharaj, Vedhant (My University, 2016)
India is currently undergoing a rapid transformation economically, consciously and spatially. A layout of national infrastructure is happening at a pace which may be ungovernable, in its current state and India’s historical and natural landscapes are in jeopardy. One such ecological resource is the Ganga (colonialised as the Ganges), which through continued pollution is reaching a point of irreversible damage. There is, however, still hope. Accordingly, this thesis moves from an overview of India in the globalised world, through a rephrasing of how “development” is understood and manifests itself to the suggestion of an overall plan to understand and implement it in a way that is co-ordinated in intention but regionally and contextually responsive in application. Through Homi Bhabha’s theoretical perspective of cultural hybridisation the discourse of creating a new infrastructural identity for India is introduced. The current political focus on the Ganga, created by India’s Prime Minister, Narendra Modi, through a renewed and trending agenda for cleaning the holy river, acts as a platform to explore the possibilities of infrastructure within this context . The Ganga River has been a religious symbol for millennia and the life force to approximately 500 million people. Through continued and increased pollution the quality of its water now radically exceeds the minimum requirements for safe drinking, bathing or even agricultural use. The Ganga River symbolises a cosmological relationship between people and the ecological environment, which requires that pollution be approached from a holistic viewpoint responding to the weight of its cultural value. This contextualized approach has the potential to become a catalyst for new innovative approaches to the integration of infrastructure throughout the river network . By using the political momentum created in the city, by the national project, this thesis is realised through a multiplicity of conflicting lenses inherent to Varanasi, one of India’s holiest cities. The city itself is growing economically but at the price of its prized ancient heritage. It possesses a cosmological value unparalleled by any other city in the country thus making it an emotionally powerful tool to mobilise a cleaning project for the river. If infrastructure is not implemented correctly the threat to the city’s unique character becomes real. This challenge created the Meta question for my research: How do you implement infrastructure into the sacred landscape? Through various degrees of research, both intuitive and informed, a system to clean water is designed in a way that truly integrates into a cultural landscape. The proposed design establishes itself as the first intervention in a national network for cleaning the River. By taking into account the infrastructural, ecological and sociological requirements of the city and its daily life the water purification sanctuary mediates the conflicting programmatic requirements between spirituality and science. Through an understanding that purity of water has a number of connotations within the site context the building utilises various treatment methods to reinforce the sanctity ABSTRACT of water through a hybrid mediation of heritage, nature, science and infrastructures (both vernacular and modern). This new typology enables the interaction of people with water cleaning infrastructure at a local scale and offers a way forward in redefining a national identity that is bound up in these currently conflicting imperatives.
Thesis (M.Arch (Professional)--University of the Witwatersrand, Faculty of Engineering and the Built Environment, 2016.
Keywords: Varanasi (India)--Religious life and customs; India--Religion; India--Social life and customs